Regulation of nicotine-induced cyclooxygenase-2 protein expression in human gingival fibroblasts - Ho Yung-chuan; Chang Yu-chao (Acta Pharmacologica Sinica; Vol 27, No 4 (April 2006): Acta Pharmacologica Sinica, 2016)
Aim: Activation of cyclooxygenase-2 (COX-2) expression by nicotine suggests a potential role for nicotine in the pathogenesis of smoking-associated periodontal disease. The aim of this study was to investigate whether chemical interactions can modulate nicotine-induced COX-2 expression in human gingival fibroblasts (HGF). Methods: Cytotoxicity was investigated by using lactate dehydrogenase leakage assays and Western blotting was used to assess COX-2 expression. Furthermore, buthionine sulfoximine (BSO; an intracellular glutathione synthesis inhibitor), 2-oxothiazolidine-4-carboxylic acid (OTZ; the precursor of cysteine), and PD98059 (extracellular signal-regulated protein kinase inhibitor) were added to search for the possible regulation mechanisms of nicotine-induced COX-2 expression. Results: Nicotine was found to elevate lactate dehydrogenase leakage in a dose-dependent manner (P